Anal dysplasia and HIV shedding in ART-treated men. (6th January 2020) - Choi, Yoojin; Salit, Irving; Grech, Sarah; Sano, Marie; Weiss, Edward; Kovacs, Colin; Paquette, Rachelle; Claudio, Marian; Gibbons, Suzanne; Severini, Alberto; Kaul, Rupert
Abstract : Objectives: Anal human papillomavirus (HPV) infection is highly prevalent among men who have sex with men (MSM). HPV-associated anal dysplasia has been linked with anal HIV RNA shedding despite antiretroviral therapy (ART). Since mucosal HIV levels are a key determinant of sexual transmission of the virus, this would have important public health implications. Therefore, we assessed the association between anal dysplasia and HIV shedding in ART-treated MSM from Toronto, Canada. Methods: In 54 HIV-infected men on effective ART, we assessed anal HIV RNA shedding by PCR, HPV infection by microsphere-based genotyping and anal dysplasia by high-resolution anoscopy. All participants were enrolled between May 2017 and October 2018. Results: The median duration of ART at the time of study enrolment was 18 years, with most participants being on an integrase inhibitor-based ART regimen. Low-level anal HIV RNA shedding was present in 15/54 (27.8%) participants. Neither the detection of shedding nor the level of HIV RNA was associated with anal dysplasia, HPV infection or antiretroviral regimen. Conclusions: HPV-associated anal dysplasia was not associated with anal HIV RNA shedding in this relatively small cohort of men on effective ART. While anal HIV RNA was detected more often than anticipated, shedding was low level and unlikely to cause HIV transmission. However, the immunological drivers of anal HIV RNA shedding in ART-treated individuals may merit further study.